ECOLOGICALLY SAFETY STORAGE OF HIGH-SULFUR COAL WASTES AND TECHNOLOGIES OF THEIR PROCESSING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
There are shown the data on composition and technological properties of solid wastes with high sulphur contents after coal mining and preparation (SCWHS) in Russia. The natural processes causing the pollution of the environment due to contents of sulphur and some potentially toxic elements in these wastes are considered. However these wastes may be promising as raw materials for producing some saleable products. According to Russian regulation a payment for wastes storing depends on so called their class of danger (CD). Methods for the CD determination for coal wastes are described. Results of simulating of thermal treatment in different conditions of SCWHC are shown. Using these results some processes of SCWHS utilization are proposed to produce some valuable products. Some new criteria based on Russian regulations are worked out to determine an ecological danger of mine waters of Russian enterprises and promising methods of mine waters cleaning and utilization. There were conducted experimental investigations on the localization of ecologically dangerous products forming due to interaction of SCWHS with waters flowing through SCWHS damps. Some carbonate rocks and fly ashes were tried for this purpose. There were found that the localization is occurred due to forming of new minerals along with a delaying of the oxidation of sulphides containing in SCWHS. Using these results grounds of some methods are proposed to decrease concentrations of ecologically toxic elements ( Fe, Al, Ni, Cu, Cr, Zn, As, Pd und oth.) till values considerably less than permitted ones in waters flowing through SCWHS damps. New promising results of experiments on laboratory and industrial installations were got for using these technologies with carbonate rocks for enterprises in central Russia.